Kompetensi Pedagogik Guru dalam Menghadapi Anak dengan Keterlambatan Bicara pada Anak Usia 4-5 Tahun - Intan Kharisma Andy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to describe teachers’ pedagogical competence in dealing with children aged 4–5 years who experience speech delay at PAUD Anak Ceria Surabaya. The research focuses on five aspects of pedagogical competence: understanding children’s characteristics, curriculum development, implementation of educative learning activities, communication with children, and assessment and evaluation of children’s development. A qualitative approach with a case study design was employed. The research subjects consisted of three early childhood teachers who directly handled children with speech delay. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data analysis followed an interactive model involving data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation.The findings indicate that teachers demonstrate strong pedagogical competence in understanding the characteristics of children with speech delay through observation of nonverbal responses, expressions, and learning engagement. Teachers are able to design flexible and adaptive learning activities, apply play-based learning approaches, use alternative communication strategies, and conduct continuous developmental assessments. However, the development of more individualized written curriculum planning still requires improvement. This study concludes that flexible and responsive pedagogical competence plays a crucial role in creating inclusive and meaningful learning experiences for children with speech delay.